MECHANISM OF SOLID-LIQUID INTERFACIAL REACTIONS - THE DISSOLUTION OF BENZOIC-ACID IN AQUEOUS-SOLUTION - Compton, R; Harding, M; Pluck, M; Atherton, J; Brennan, C (1993)
The kinetics of dissolution of benzoic acid into aqueous solution are studied using the channel flow cell method. In contrast to alternative experimental approaches the method is shown to provide interfacial rate data permitting mechanistic insight. Kinetic parameters are reported. © 1993 American Chemical Society.